2018
DOI: 10.1080/21691401.2018.1431652
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Bifidobacterium bifidum BB01 by xanthan–chitosan: preparation and its stability in pure milk

Abstract: Xanthan-chitosan (XC) and xanthan-chitosan-xanthan (XCX) were employed for microencapsulation of Bifidobacterium bifidum BB01 using extrusion technique. To optimize the process of B. bifidum BB01 microcapsules based on XC hydrogels, response surface methodology was employed to obtain the best possible combination of chitosan concentration, xanthan-B. bifidum BB01 mixture (XBM)/chitosan, stirring time for the maximum viable count and encapsulation yield. The optimum conditions were: chitosan concentration of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Here, we found that adding XG effectively improved this phenomenon. XG has good macromolecular special structure and colloidal properties and is often used as a microencapsulation material ( 38 ). Microspheres prepared from SA and CaCl 2 are prone to tailing and irregular shapes ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that adding XG effectively improved this phenomenon. XG has good macromolecular special structure and colloidal properties and is often used as a microencapsulation material ( 38 ). Microspheres prepared from SA and CaCl 2 are prone to tailing and irregular shapes ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the microencapsulation of Lactobacillus casei Shirota in gum Arabic even increases the bacteria count during storage; for example, applied in a pudding for 14 days in refrigeration increased bacteria from 8.27 to 9.16 log CFU/g and in chocolate milk for 180 days at 25 °C increased to >8 log CFU/g [ 58 ]. In pure milk, the encapsulation of B. bifidum BB01 bacteria in xanthan gum and chitosan increases by 0.5 log CFU/g over 21 days of milk storage at 4 °C [ 59 ]. In mature cheeses of the gouda type, a count of 10 8 CFU/g of Bifidobacterium lactis is maintained for 40 days after microencapsulation in cyclodextrin and gum Arabic, and the microcapsule also adds fiber (1%) [ 60 ].…”
Section: Microcapsules In Functional Foodsmentioning
confidence: 99%
“…This is possible by exploiting the electrostatic interaction between anionic xanthan gum and cationic chitosan. For example, Shu et al (2018aShu et al ( ,2018b dispersed Bifidobacterium bifidum in xanthan gum hydrogel and extruded the blend into a chitosan solution to obtain capsules, which improved the survival of B. bifidum in milk. By alternating between xanthan gum solution and chitosan solution, the amount of coating layers can be modified.…”
Section: Encapsulation and Controlled Release Formulations With Xanthan Gummentioning
confidence: 99%
“…By alternating between xanthan gum solution and chitosan solution, the amount of coating layers can be modified. The beneficial effect of an additional layer was shown for Lactobacillus acidophilus in xanthan-chitosan capsules, resulting in a better control of the release as well as improved viability during storage in a dairy beverage and exposure to simulated gastric juice (Shu et al, 2018a(Shu et al, ,2018b.…”
Section: Encapsulation and Controlled Release Formulations With Xanthan Gummentioning
confidence: 99%